Theoretical treatment of the resonant hyper-Raman scattering of light in crystals - Semenova, L.E.; Prokhorov, K.A. (Functional Materials, 2004)
The work is aimed at discussion of different mechanisms of the resonant hyper-Raman scattering of light with participation of excitons in semiconductor crystals and analysis of their contributions to the scattering intensity. Работа посвящена обсуждению различных механизмов резонансного гиперкомбинационного рассеяния света с участием экситонов в полупроводниковых кристаллах и анализу их вкладов в интенсивность рассеяния. Роботу присвячено обговоренню різних механiзмiв резонансного гіперкомбінаційно-го розсіяння світла за участю екситонів у напівпровідникових кристалах та аналізу їх внесків в інтенсивність розсіяння.